البنية الحكائية في السرد الشعبي نماذج مختارة من الحكايات الشعبية - بشي، راضية, دركي، زينب; تواوة، هاجر (University of El-oued, 2022)
تناولت هذه الدراسة الموسومة بـ "البنية الحكائية في السرد الشعبي الجزائري – نماذج مختارة من الحكايات الشعبية -"موضوع الحكاية الشعبية من حيث مفهومها ومكوناتها السردية وبنيتها الحكائية. ففي الجانب النظري القائم على استعمال آلية الوصف في التحليل، تطرقت الدراسة بصفة خاصة إلى آلية الزمن الذي يعد المحور الأساسي والقالب الذي تبنى عليه الأحداث، وكذا آلية المكان الذي يوفر المساحة الواسعة لتحرك شخصيات الحكاية و تطور أحداثها. أما في الجانب التطبيقي فقد ركزت الدراسة على تحليل الحكاية الشعبية من خلال استخدام أدوات التحليل الإجرائي البنيوي القائم على المقاربة البنيوية في التحليل السردي للنص الحكائي حيث قدمت الدراسة ثلاث نماذج من الحكائيات الشعبية تم إخضاع بنياتها للتحليل السردي. This study, tagged with "The Narrative Structure in the Algerian Popular Narrative - Selected Models -" dealt with the topic of the folk tale in terms of its concept, narrative components and narrative structure. In the theoretical aspect based on the use of the mechanism of description in the analysis, the study dealt in particular with the mechanism of time, which is the main axis and the template on which events are built, as well as the mechanism of the space that provides the wide space for the movement of the characters of the story and the development of its events. As for the practical aspect, the study focused on analyzing the folk tale through the use of structural procedural analysis tools based on the structural approach in the narrative analysis of the narrative text. The study presented three models of folk tales whose structures were subjected to narrative analysis.
Keywords: الحكائية، السرد الشعبي ، الحكايات الشعبية